ARTERIOGENESIS DAN ANGIOGENESIS PADA STROKE HEMORAGIK:MEMPERTAJAM KONSEP UNTUK MEMPEROLEH MANFAAT TERBAIK NEOVASKULARISASI * - Lyrawati, Diana (Jurnal Kedokteran Brawijaya, 2008)
Arteriogenesis and angiogenesis contribute both to  the damage and repair in hemorrhagic stroke. Understanding and unraveling the fundamental and mechanisms of these processes should facilitate the development of treatment strategies to improve outcome after stroke. This article describes briefly the basic principles of arteriogenesis and angiogenesis completed with some key molecular players, followed by aperspective of the author on how to use those neovascularization to benefit repair and recovery processes in post-hemorrhagic stroke. Key Words : arteriogenesis, angiogenesis, hemorrhagic, stroke